Pengembangan Produk Rotan Berbasis Nilai Tambah: Perspektif dan Kepuasan Konsumen di Rotan Rangga Kota Baru - Sinaga, Threeatmi Ulin; Wahyudi, Rizqi; Astari, Ni Putu Widya; Lubis, Marwah Agus; Afizah, Anisa Fikratul; Saragih, Febi Nissa; Ulfa, Helza Maria; Sipahutar, Erika Jelita; Ariesta, Anggun Vica; Mardiono, Intan (Westscience Press, 2025)
This research is motivated by the shift in market demand for rattan furniture, which not only needs to be functional but must also possess aesthetic and sustainability value. The objective is to analyze value-added product development strategies and the level of consumer satisfaction at Rotan Rangga Kota Baru. The study employs a qualitative approach (interviews and direct observation) for preliminary data and a descriptive quantitative approach using the Quality Function Deployment (QFD) and House of Quality (HoQ) methods for product planning. The results indicate that product development successfully enhances value-added through design innovation, quality materials, and production efficiency. The main factors influencing consumer satisfaction are quality, aesthetics, comfort, durability, and the aspect of environmental sustainability. Through HoQ analysis, the customer attribute with the highest importance is